Diseño de un plan de desarrollo sostenible para la crianza de cerdo en el hato porcino de la ESPAM MFL - Pinargote Párraga, Jesús Manuel (2014)
The main objective of this thesis is the design of a sustainable development plan for raising pigs in the pig herd of ESPAM MFL, which offers live hogs to the highest quality and hygiene, the pork in the today is not only tasty but also healthy, currently producing the same it is performing technically improving genetics and careful feeding the pigs, the target market are the inhabitants of the city of knitting, there is high demand currently unmet pork. The process of production and marketing is done as required by the health technical standards, with highly trained and motivated staff , being responsible to the environment and the community , conducting an internal situational analysis to determine the levels of production and reproduction by swine SWOT matrix , together with a plan that control and planning for sustainable development of the pig herd in which the internal and external forces that interact in this process and then socialize the project with the persons involved was determined was designed to pig breeding Sock city Region Bolivar , performing the respective surveys aimed at the population in order to serve as a support for the investment of swine reproduction.